A new method for rainfall estimation through soil moisture observations. Issue 5 (6th March 2013) - Brocca, L.; Moramarco, T.; Melone, F.; Wagner, W.
Abstract [1] Rainfall and soil moisture, SM, are two important quantities for modeling the interaction between the land surface and the atmosphere. Usually, rainfall observations are used as input data for modeling the time evolution of SM within hydrological and land surface models. In this study, by inverting the soil‐water balance equation, a simple analytical relationship for estimating rainfall accumulations from the knowledge of SM time series is obtained. In situ and satellite SM observations from three different sites in Italy, Spain, and France are used to test the reliability of the proposed approach in contrasting climatic conditions. The results show that the model is able to satisfactorily reproduce daily rainfall data when in situ SM observations are employed (correlation coefficient, R, nearly equal to 0.9). Furthermore, also by using satellite data reasonable results are obtained in reproducing 4 day rainfall accumulations with R‐values close to 0.8. Based on these preliminary results, the proposed approach can be adopted conveniently to improve rainfall estimation at a catchment scale and as a supplementary source of data to estimate rainfall at a global scale.